The relationship between mindfulness and metacognitive beliefs with emotional intelligence - Farahnaz Koohneshin Taromi; Shima Parandin (Social Determinants of Health, 2017)
Background: Emotional intelligence is a set of teachable abilities and skills that prepare people for the sustainability and success in life. The purpose of the present study was to predict the emotional intelligence based on metacognitive beliefs and mindfulness beliefs in the students.